Cognitive and affective control for adolescents in care versus their peers: implications for mental health - Rosie McGuire; Sarah L. Halligan; Susanne Schweizer; Jovita T. Leung; Rachel M. Hiller (BMC, 2023)
Abstract Background Many adolescents who have been removed from the care of their biological parent(s) and placed in State or Local Authority care have experienced significant adversity, including high rates of maltreatment and other trauma(s). As a group, these young people experience far higher rates of mental health difficulties compared to their peers. While their mental health outcomes are well-documented, little is known about mechanisms that may drive this. One potential mechanism, linked to both trauma and adversity exposure and mental health, is affective control (the application of cognitive control in affective contexts). Methods We compared cognitive and affective control in 71 adolescents (65% girls) in care aged 11-18 (M = 14.82, SD = 2.10) and 71 age and gender-matched peers aged 11-19 years (M = 14.75, SD = 1.95). We measured cognitive and affective control using standard experimental tasks, and for those in care, we also examined associations with self-reported emotion regulation, mental health, and school well-being. Results After controlling for IQ, there was a significant group difference in affective control performance, with those in care on average performing worse across all tasks. However, further analyses showed this was driven by deficits in overall cognitive control ability, and was not specific to, or worsened by, affective stimuli. Further, we found no evidence that either cognitive or affective control was associated with emotion regulation abilities or the mental health and well-being of young people in care. Conclusions Results suggest that cognitive and affective control may not underlie mental health for young people in care, though limitations should be considered. We discuss implications for theory and intervention development, and avenues for further research. Trial registration: https://doi.org/10.17605/OSF.IO/QJVDA